2013
DOI: 10.1177/1934578x1300800919
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Activities of α-Mangostin on Peripheral Blood Mononuclear Cells

Abstract: Mangosteen (Garcinia mangostana L.) a tropical fruit, has been used in traditional medicine. A frequently used part of mangosteen is the pericarp, containing a high content of xanthones. α-Mangostin, one of the major xanthone derivatives, exhibits a variety of actions, including antimicrobial, antioxidant, cytotoxic and antitumor; however, its function on the immune system is still equivocal. This study aimed to examine the immunomodulatory activities of α-mangostin on lymphocyte lineage and cytokine productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
2
9
0
1
Order By: Relevance
“…Sufficient evidence has suggested that the anti-inflammatory properties of MAN in vivo is closely related to its effects on cytokines profiles and macrophages seem to be its main target. 13 , 14 This notion was supported by our previous study, as MAN exhibited promising therapeutic effects on ALI, which is believed to be mainly mediated by macrophages. 3 Because macrophages do not only sense and cope with infections directly, but also initiate adaptive immune reactions by functioning as antigen presenting cells.…”
Section: Discussionsupporting
confidence: 58%
“…Sufficient evidence has suggested that the anti-inflammatory properties of MAN in vivo is closely related to its effects on cytokines profiles and macrophages seem to be its main target. 13 , 14 This notion was supported by our previous study, as MAN exhibited promising therapeutic effects on ALI, which is believed to be mainly mediated by macrophages. 3 Because macrophages do not only sense and cope with infections directly, but also initiate adaptive immune reactions by functioning as antigen presenting cells.…”
Section: Discussionsupporting
confidence: 58%
“…The reduction PBMC treated with different concentrations of PF-FPLC occurs by an interaction between cellular sensitivity and protein chemical structure. However, the reduction in viability caused by PF-FPLC is acceptable since there are compounds which present a viability reduction in small concentrations; paclitaxel is an example (Kasemwattanaroj et al, 2013). The PF-FPLC proteins showed an effect on the decreased viability of PBMC directly proportional to test concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Peningkatan aktivitas proliferasi sel leukosit dibuktikan dengan peningkatan persentase viabilitas sel saat diuji dengan MTT assay sebesar 208,485 ± 21,21 dan 361,818 ± 86,37, yang ditampilkan pada gambar 2. Kasemwattanaroj et al, [15]mendapatkan bahwa senyawa α-mangostin pada sangat sitotoksik terhadap kultur sel leukosit mononuklear manusia dengan IC50 5,55 μg/mL. Namun ketika sel leukosit diberi perlakuan dengan mitogen pemicu proliferasinya dan α-mangostin, tingkat proliferasi sel leukosit meningkat dan meregulasi pelepasan sitokin proinflamasi.…”
Section: Hasil Dan Diskusiunclassified